Strategi Pembelajaran dalam Perspektif Islam - Junaidah, Junaidah (Universitas Islam Negeri Raden Intan Lampung, 2015)
National education in the face of crisis, relating to quality relevance and effefficiency ofexternallitisme, and management. A further proposed at least the issue of national education systems: (1) behavior morale students, (2) the distribution of the study , (3) arestill education sy stem internal, lack of efficiency (4) the organizational, ( 5 ) the management ofeducation is not consistent with the development of a national (6) Resources not professional. One side weakness who handled Abudin Nata is concerned by the lack of a strategy for learning, but the strategy of hold important roles in the success learning process.The purpose this is journal ia lesson in Islam he thought Abuddin Nata perspective. Result of search for a literature indicate a lesson in islam's perspective is its base in the preliminary framework changes expected to be on the educational objectives on the establishment of such behavior in a student. The approach in learning is part of a strategy of learning that this approachusing a yardstick a science discipline objectives to be achieved, measures to be used, or mark used, this approach with regard to the teaching and learning is most properly and effectivel y to achieve the target.In the implementation of the acquisition may be conducted through the model of islamic education oriented to approach cbsa skills and learning process, quantum teaching, problem solving and the formation of memories.